Blockchain-Based Smart Contracts in Microfinance: Enhancing Trust and Reducing Transaction Costs in Southeast Asia - Farida Akbarina; Nina Anis; Rashid Rahman (Yayasan Adra Karima Hubbi, 2025)
Microfinance plays a vital role in financial inclusion in Southeast Asia, yet persistent challenges such as high transaction costs, information asymmetry, and limited transparency continue to undermine institutional sustainability and borrower trust. This study aims to examine how blockchain-based smart contracts enhance trust and reduce transaction costs within microfinance institutions operating in Southeast Asia. A mixed-methods research design is employed, combining quantitative analysis of transaction cost indicators, loan processing efficiency, and repayment performance with qualitative insights from microfinance practitioners and borrowers. Data are collected from selected institutions implementing smart contract systems in Indonesia, Vietnam, and the Philippines. The results indicate significant reductions in administrative, monitoring, and enforcement costs alongside faster loan disbursement processes. Improved transparency and automated contract execution contribute to higher levels of borrower trust, fewer disputes, and stronger repayment discipline. The findings reveal a positive relationship between transaction cost reduction and trust enhancement, suggesting that operational efficiency reinforces institutional credibility. The study concludes that blockchain-based smart contracts function as socio-technical mechanisms that reshape governance structures in microfinance rather than serving solely as efficiency tools. The novelty of this research lies in its empirical demonstration that technological trust embedded in smart contracts can complement and partially replace relational trust, offering a context-sensitive framework for digital financial inclusion in Southeast Asia.